2009
DOI: 10.1590/s1806-37132009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de pectus carinatum e pectus excavatum em escolares de Manaus

Abstract: OBJETIVO: Determinar a prevalência das deformidades congênitas da parede torácica anterior em escolares de 11 a 14 anos. MÉTODOS: Participaram do estudo escolares da rede estadual de ensino da cidade de Manaus (AM). Para a composição de uma amostra estatisticamente significativa, com precisão de 1% e IC95%, foram incluídos 1.332 escolares. A deformidade pectus foi identificada através de exame físico do tórax, e os indivíduos com esta deformidade responderam a um questionário com questões sobre hereditariedade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 14 publications
0
26
1
Order By: Relevance
“…In the present study, nearly half of the patients had a positive family history. However, in our study, we found fewer patients with scoliosis than has been reported in previous studies (16%–51%) [ 18 ]. Other anomalies are well known to be associated with these deformities (e.g., kyphosis, cardiac anomalies, and foot anomalies) [ 2 ].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In the present study, nearly half of the patients had a positive family history. However, in our study, we found fewer patients with scoliosis than has been reported in previous studies (16%–51%) [ 18 ]. Other anomalies are well known to be associated with these deformities (e.g., kyphosis, cardiac anomalies, and foot anomalies) [ 2 ].…”
Section: Discussioncontrasting
confidence: 71%
“…The prevalence of a family history may be very high, potentially reaching up to 40% in patients with PE [ 17 ]. In a study from Brazil, a family history of pectus deformities was found in 65% of patients [ 18 ]. In the present study, nearly half of the patients had a positive family history.…”
Section: Discussionmentioning
confidence: 99%
“…A search of previous publications revealed that the prevalence of pectus excavatum in dogs has not been reported; however, in cats it was found to be 2.05% (5/244) [15] and in humans 1.0–1.27% [16, 17]. Although the present study did not primarily focus on the incidence of pectus excavatum, 0.33% of puppies (8 out of 2,443) were found to have pectus excavatum.…”
Section: Discussionmentioning
confidence: 99%
“…Although we excluded patients having Marfan’s disease and other connective tissue disorders, the incidence of scoliosis with a Cobb angle> 10° was much higher than that in ordinary population, yielding 17.6% in our pectus excavatum patients. Akcali et al [5] reported that scoliosis was associated with pectus deformities in 13.5% of his surveyed students recruited from public schools in Manaus, Brazil [10]. The scoliosis incidences discovered in teenagers during routine check-ups in Guangzhou and Xi’an were 1.07% and 1.33%, respectively [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of pectus excavatum and scolosis has drawn much attention recently. Many reports have shown the coexistence of pectus excavatum and scoliosis in teenagers [4] and adults [5,6]. So far, the exact cause for the coexistence has remained unknown.…”
Section: Introductionmentioning
confidence: 99%